Food-borne viruses : progress and challenges - Koopmans, M. P. G.; Cliver, Dean O.; Bosch, Albert (ASM Press, 2008)
Food-borne viruses are recognized as a major health concern, but their distribution, definition, and impact are poorly understood. The volume Food-Borne Viruses goes a long way in correcting that problem. Written by leading scientists in the field, it brings together the latest knowledge on these viral strains, their detection and control, and associated challenges.
Keywords: Foodborne diseases.; Virus diseases.; Food -- Microbiology.; elektronické knihy; electronic books